2001
DOI: 10.1128/jvi.75.17.7875-7881.2001
|View full text |Cite
|
Sign up to set email alerts
|

Influenza Virus NS1 Protein Induces Apoptosis in Cultured Cells

Abstract: The importance of influenza viruses as worldwide pathogens in humans, domestic animals, and poultry is well recognized. Discerning how influenza viruses interact with the host at a cellular level is crucial for a better understanding of viral pathogenesis. Influenza viruses induce apoptosis through mechanisms involving the interplay of cellular and viral factors that may depend on the cell type. However, it is unclear which viral genes induce apoptosis. In these studies, we show that the expression of the nons… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
123
2
1

Year Published

2004
2004
2022
2022

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 150 publications
(130 citation statements)
references
References 68 publications
4
123
2
1
Order By: Relevance
“…The viral neuraminidase protein was the first influenza virus protein shown to have a role in the induction of apoptosis (Schultz-Cherry & Hinshaw, 1996). The NS1 protein has also been shown to have proapoptotic features (Lam et al, 2008;Schultz-Cherry et al, 2001). However, these data conflict with the finding that NS1 has anti-apoptotic functions (Ehrhardt et al, 2007;Shin et al, 2007c;Zhirnov et al, 2002).…”
Section: Introductioncontrasting
confidence: 55%
“…The viral neuraminidase protein was the first influenza virus protein shown to have a role in the induction of apoptosis (Schultz-Cherry & Hinshaw, 1996). The NS1 protein has also been shown to have proapoptotic features (Lam et al, 2008;Schultz-Cherry et al, 2001). However, these data conflict with the finding that NS1 has anti-apoptotic functions (Ehrhardt et al, 2007;Shin et al, 2007c;Zhirnov et al, 2002).…”
Section: Introductioncontrasting
confidence: 55%
“…The mechanisms of virus-induced cell damage which is followed by cell death are not well understood [23]. Apoptosis induced by influenza viruses has been shown in a variety of cell lines [21,29,30]. Several viral factors, including M1, NS1, and NA proteins, have been reported to be related to apoptosis induction [13,16,30].…”
Section: Introductionmentioning
confidence: 99%
“…Given that the relationship between influenza A virus, NS1 and apoptosis has been described in a number of studies, [22][23][24] we compared the effects of different H5N1-NS1 variants on the apoptotic response of Hela cells. As seen in Figure 6a, although the percentage of both earlyapoptotic cells (which possess a single-positive staining pattern detected by FITC-labeled annexin V) and late-apoptotic/necrotic cells (annexin V/PI double-positive staining pattern) were mildly elevated upon expression H5N1-NS1 variants relative to the controls, release of monoor oligonucleosomes from apoptotic cells was unchanged (Figure 6b).…”
Section: H5n1-ns1 Variants Had No Significant Influence On the Apoptomentioning
confidence: 99%
“…It has been shown that the overexpression of H5N9 NS1 in MDCK or Hela cells is sufficient to trigger apoptosis. 22 Transfection of NS1 from the A/HK/483/97(H5N1) strain into human airway epithelial cells can also induce apoptosis. 23 However, in another report, the ectopic expression of PR8/NS1 protein was shown to produce an antiapoptotic response in MDCK cells through the activation of the PI3K/Akt signaling pathway.…”
Section: Effects Of H5n1-ns1 Variants On Ifn Inductionmentioning
confidence: 99%